Community Health Workers and Use of mHealth: Improving Identification of Pregnancy Complications and Access to Care in the Dominican Republic. Issue 3 (May 2018) - Bonnell, Susan; Griggs, Anne; Avila, Gloria; Mack, Jonathan; Bush, Ruth A.; Vignato, Julie; Connelly, Cynthia D.
This article presents the feasibility and acceptability of using mobile health technology by community health workers (CHWs) in San Juan Province, Dominican Republic, to improve identification of pregnancy complications and access to care for pregnant women. Although most women in the Dominican Republic receive four antenatal care visits, poor women and adolescents in remote areas are more likely to have only one initial prenatal visit to verify the pregnancy. This community-based research began when community leaders raised concern about the numbers of their mothers who died in childbirth annually; San Juan's maternal mortality rate is 144/100, 000 compared to the Caribbean rate of 85/100, 000. Eight CHWs in three communities were taught to provide third-trimester antenatal assessment, upload the data on a mobile phone application, send the data to the local physician who monitored data for "red flags, " and call directly if a mother had an urgent problem. Fifty-two pregnant women enrolled, 38 were followed to delivery, 95 antenatal care postintake were provided, 2 urgent complications required CHW home management of mothers, and there were 0 deaths. Stakeholders endorsed acceptability of intervention. Preliminary data suggest CHWs using mobile health technology is feasible, linking underserved and formal health care systems with provision of primary care in mothers' homes.